Knockdown of AKT3 (PKBγ) and PI3KCA Suppresses Cell Viability and Proliferation and Induces the Apoptosis of Glioblastoma Multiforme T98G Cells - Monika Paul-Samojedny (BioMed Research International, 2014)
Glioblastoma multiforme (GBM) is the most malignant and invasive human brain tumor that is difficult to treat and has a very poor prognosis. Thus, new therapeutic strategies that target GBM are urgently needed. The PI3K/AKT/PTEN signaling pathway is frequently deregulated in a wide range of cancers. The present study was designed to examine the inhibitory effect of AKT3 or PI3KCA siRNAs on GBM cell growth, viability, and proliferation.T98G cells were transfected with AKT3 and/or PI3KCA siRNAs. AKT3 and PI3KCA protein-positive cells were identified using FC and Western blotting. The influence of specific siRNAs on T98G cell viability, proliferation, cell cycle, and apoptosis was evaluated as well using FC. Alterations in the mRNA expression of AKT3, PI3KCA, and apoptosis-related genes were analyzed using QRT-PCR. Knockdown of AKT3 and/or PI3KCA genes in T98G cells led to a significant reduction in cell viability, the accumulation of subG1-phase cells and, a reduced fraction of cells in the S and G2/M phases. Additionally, statistically significant differences in the BAX/BCL-2 ratio and an increased percentage of apoptotic cells were found. The siRNA-induced AKT3 and PI3KCA mRNA knockdown may offer a novel therapeutic strategy to control the growth of human GBM cells.